How insider CEOs succeed - Chastain, Andrew P. and Watkins, Michael D. (Harvard Business Review)
When an organization taps one of its current executives to be its new CEO, the transition might seem straightforward. The promotion is often the culmination of years$1 (Bmaybe decades$1 (Bof hard work. CEOs who come from inside the company have probably served in the C-suite or run a large division before, so they have relationships with everyone in top management and the confidence of the board. They know the organization, its history, and its culture. They understand its strategy and might have been intimately involved in developing it. They$1 (Bve established credibility and support. You$1 (Bd think, then, that they$1 (Bd have an easier time adjusting to and excelling in the job than external hires would. - Reproduceds
Keywords: Leaders